The effect of myofascial release on heart rate variability in subjects with autonomic dysfunction: a randomized controlled trial - Tatyana V. Kazantseva; Olga I. Kolomiets (Вестник восстановительной медицины)
INTRODUCTION. Autonomic dysfunction (AD) is characterized by changes in the afferent or efferent components of sympathetic and parasympathetic neural control that are associated with pathological conditions. Heart rate variability (HRV), as one of the key indicators of autonomic regulation, is known to be associated with many chronic diseases and mortality. Thus, interventions aimed at improving autonomic regulation and increasing HRV are important for public health. Myofascial release (MFR) — a form of self-massage aimed at relieving tension, reducing pain, and increasing range of motion, can have a positive effect on autonomic regulation.